Effects of core strength training using stable versus unstable surfaces on physical fitness in adolescents: a randomized controlled trial - Granacher, U.; Schellbach, J.; Klein, K.; Prieske, O.; Baeyens, J.-P.; Muehlbauer, T. (BMC Sports Science, Medicine and Rehabilitation, 2014)
Background: It has been demonstrated that core strength training is an effective means to enhance trunk muscle strength (TMS) and proxies of physical fitness in youth. Of note, cross-sectional studies revealed that the inclusion of unstable elements in core strengthening exercises produced increases in trunk muscle activity and thus provide potential extra training stimuli for performance enhancement. Thus, utilizing unstable surfaces during core strength training may even produce larger performance gains. However, the effects of core strength training using unstable surfaces are unresolved in youth. This randomized controlled study specifically investigated the effects of core strength training performed on stable surfaces (CSTS) compared to unstable surfaces (CSTU) on physical fitness in school-aged children. Methods: Twenty-seven (14 girls, 13 boys) healthy subjects (mean age: 14 ± 1 years, age range: 13-15 years) were randomly assigned to a CSTS (n = 13) or a CSTU (n = 14) group. Both training programs lasted 6 weeks (2 sessions/week) and included frontal, dorsal, and lateral core exercises. During CSTU, these exercises were conducted on unstable surfaces (e.g., TOGU© DYNAIR CUSSIONS, THERA-BAND© STABILITY TRAINER). Results: Significant main effects of Time (pre vs. post) were observed for the TMS tests (8-22%, f?=?0.47-0.76), the jumping sideways test (4-5%, f = 1.07), and the Y balance test (2-3%, f = 0.46-0.49). Trends towards significance were found for the standing long jump test (1-3%, ?= 0.39) and the stand-and-reach test (0-2%, f = 0.39). We could not detect any significant main effects of Group. Significant Time x Group interactions were detected for the stand-and-reach test in favour of the CSTU group (2%, f = 0.54). Conclusions: Core strength training resulted in significant increases in proxies of physical fitness in adolescents. However, CSTU as compared to CSTS had only limited additional effects (i.e., stand-and-reach test). Consequently, if the goal of training is to enhance physical fitness, then CSTU has limited advantages over CSTS.